A study of hippocampal T2 relaxometry value in temporal lobe epilepsy patient - Basri, Niemah (2023)
Background: In the advance of the current imaging technique for the detection of mesial temporal sclerosis for temporal lobe epilepsy patient, there are multiple quantitative techniques for Magnetic resonance imaging (MRI). One of the long known to be valuable technique is T2 relaxometry study where there is overall better accuracy for detection of mesial temporal sclerosis if compared with the qualitative assessment only. Methods: This is a comparative cross-sectional study that was conducted at the Hospital Universiti Sains Malaysia, Kubang Kerian. A total of 51 participant were included in this study where 19 were temporal lobe epilepsy patients and 32 were control. Total duration of this study is one year and five months from August 2021 to January 2023. The hippocampal T2 relaxometry was calculated for control and temporal lobe epilepsy patient and the mean reading for these groups were compared. This is to get the normal value of hippocampal T2 relaxation time and abnormal value cut off point for epilepsy patient. The mean reading of T2 relaxometry for control and patient will be determine. Using Pearson correlation, the T2 relaxometry value correlation is made with age, duration of epilepsy and seizure frequency. Results: The mean T2 relaxometry for epilepsy patient was higher than control. It is also noted to be higher in right hippocampus than left hippocampus in both patient and control. For temporal lobe epilepsy patient, the reading for right and left hippocampus were 110.13 (10.51)ms and 107.15 (9.43)ms respectively. Meanwhile for control the reading for right and left hippocampus were 99.54 (4.00)ms and 97.00 (3.46)ms respectively. For correlation, moderate to good positive correlation was seen between the duration of epilepsy with T2 relaxometry of right hippocampus. Whereas poor positive correlation between the right hippocampus T2 relaxometry with age (P>0.01), as well poor positive correlation between both hippocampus T2 relaxometry with seizure frequency(P>0.01). Conclusion: T2 relaxometry is a quantitate technique that can help in detection of subtle abnormality of hippocampus. In our study, one patient was reported to has normal hippocampus by qualitative assessment but had raised T2 relaxometry which follow the clinical diagnosis of epilepsy.